Metagenomics and metabolomics analysis to investigate the effect of Shugan decoction on intestinal microbiota in irritable bowel syndrome rats - Hang, Lu; Wang, Enkang; Feng, Ya; Zhou, Yan; Meng, Yangyang; Jiang, Fengru; Yuan, Jianye (Frontiers in Microbiology, 2022)
Background: The effect of Shugan Decoction (SGD) on intestinal motility and visceral hypersensitivity in Water avoid stress (WAS)-induced IBS-D model rats has been confirmed. However, the mechanisms of its action involved in the treatment of IBS-D need to be further studied. Intestinal flora plays an important role in maintaining intestinal homeostasis and normal physiological function. Changes in the intestinal flora and its metabolites are thought to participate in the pathophysiological process of IBS. Aim: This study aimed to analyze the influence of SGD on intestinal microflora and fecal metabolites in IBS-D rats by multiple omics techniques, including metagenomic sequencing and metabolomics. Methods: We measured the intestinal motility and visceral sensitivity of three groups of rats by fecal pellets output and colorectal distension (CRD) experiment.In addition, metagenome sequencing analysis was performed to explore the changes in the number and types of gut microbiota in IBS-D model rats after SGD treatment. Finally, we also used untargeted metabolomic sequencing to screen the metabolites and metabolic pathways closely related to the therapeutic effect of SGD. Results: We found that compared with the rats in the normal group, the fecal pellets output of the rats in the WAS group increased and the visceral sensitivity threshold was decreased (P<0.05). Compared with the rats in the WAS group, the fecal pellets output of the SGD group was significantly decreased, and the visceral sensitivity threshold increased (P<0.05). Besides, compared with the rats in the WAS group, the relative abundance of Bacteroidetes increased in SGD group, while that of Firmicutes decreased at the phylum level, and at the species level, the relative abundance of Bacteroides sp. CAG:714, Lactobacillus reuteri and Bacteroides Barnesiae in SGD group increased, but that of bacterium D42-87 decreased. In addition, compared with the WAS group, several metabolic pathways were significantly changed in SGD group, including Taurine and hypotaurine metabolism, Purine metabolism, Sulfur metabolism, ABC transporters, Arginine and proline metabolism and Bile secretion. Conclusions: SGD can regulate specific intestinal microorganisms and some metabolic pathways, which may explain its effect of alleviating visceral hypersensitivity and abnormal intestinal motility in WAS-induced IBS-D rats.